Multicultural Service-Learning And Community-Based Research As a Model Approach to Promote Social Justice - Rosner-Salazar, Theresa Ann (Social justice, 2003)
Part of a special issue on applied research and social justice. The use of multicultural service-learning and community-based research as a means to improve the training received by service providers who work with diverse populations in disenfranchised communities is discussed. The benefits of employing a community-academic partnership model as part of this training are debated, and recommendations are made to assist educators, researchers, and community activists in realizing the potential of such models to promote social justice.